2008
DOI: 10.1007/s00414-007-0221-3
|View full text |Cite
|
Sign up to set email alerts
|

Textile fibres along the bullet path – experimental study on a skin-gelatine composite model

Abstract: In the past, the presence of textile fibres in the bullet track of gunshot injuries in body regions covered with clothes was used to differentiate between entrance and exit wounds; as with handguns, a displacement of textile fibres was considered possible only in the direction of the shot. In the present study, the transfer of textile fibres from the entrance and exit regions into the bullet path was systematically investigated with the help of a skin-gelatine composite model. For this purpose, the skin of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…After firing the shots, the gelatin blocks were laminated in 1-cm-thick layers and then the area of the bullet track was cut out of each slice as already described in other papers [7,10,34,35]. The excised gelatin pieces had a volume of approximately 500 μl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After firing the shots, the gelatin blocks were laminated in 1-cm-thick layers and then the area of the bullet track was cut out of each slice as already described in other papers [7,10,34,35]. The excised gelatin pieces had a volume of approximately 500 μl.…”
Section: Methodsmentioning
confidence: 99%
“…Gelatin blocks measuring 25×12×12 cm (length of the bullet path 25 cm) were prepared in accordance with the recommendations for ballistic gelatin in a 10% concentration [7,8,10,13,28,34,35]. Skin pieces from the belly region of freshly slaughtered pigs were fixed to the front ends (12×12 cm in size) of the gelatin blocks with dental instant glue (Renfert, Hilzingen, Germany) in the areas of the later entrance and exit site.…”
Section: Methodsmentioning
confidence: 99%
“…For each group (a cotton, b jeans, c leather, d nylon) and firing distance tested (5,15, and 30 cm), the macroscopic features of the fabrics and the underlying skin and the micro-CT reconstructions (frontal and lateral views) of the wounds are represented particular, it was assumed that the density of textile fibers in the bullet entrance was higher than that in the exit site. This general rule, however, has been recently questioned by Vennemann et al [26] in an experimental study performed on a porcine skin-gelatine model [27,28]. The authors observed a retrograde displacement of fibers from the clothing back into the bullet path.…”
Section: Discussionmentioning
confidence: 84%
“…The principal technical procedure has already been described in previous papers [4,7,20,21]. In order to imitate a reentry shot constellation, two cylindrical gelatine blocks (24×8 cm in size) were tightly wrapped in pieces of skin from the belly region of slaughtered pigs and arranged one behind the other by means of a metal rack which permitted the distance between the cylindrical segments to be varied (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In the bullet path of the primary target (first segment), a small number of colored particles from the exit site could be detected either within the permanent track or at the end of radial gelatine slits [20]. For the second segment, each section of the bullet track contained skin fragments which had been displaced from the reentry site in an anterograde manner [7].…”
Section: Seriesmentioning
confidence: 99%